2012
DOI: 10.1017/s1470542711000262
|View full text |Cite
|
Sign up to set email alerts
|

Structural Factors Affecting the Assignment of Word Stress in German

Abstract: This paper aims to shed light on regularities underlying German stress assignment. The results of a pseudoword production task suggest that rhyme complexity of the final syllable is a strong predictor of main stress position in German. We also found that antepenult rhyme complexity and orthographic rhyme structure have significant effect on stress assignment. In general, the effects seem to be probabilistic rather than categorical. Our results suggest that phonological theories of German word stress need to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 42 publications
3
26
0
1
Order By: Relevance
“…This result seems to lend further support to the assumption that in German antepenultimate and final stress have the same underlying foot structure, that is, a non-branching final foot containing only one heavy syllable, which is preceded by a trochee, while penultimate stress has a different underlying foot structure, that is, a final trochee preceded by an unparsed syllable (Domahs, Klein, et al, 2013;Domahs et al, 2008;Janben & Domahs, 2008;Röttger et al, 2012). In consequence, APU versus F stress patterns are phonologically more similar than APU versus PU patterns and should thus be more difficult to keep distinct in a mental representation for participants who have acquired this aspect of German phonology.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This result seems to lend further support to the assumption that in German antepenultimate and final stress have the same underlying foot structure, that is, a non-branching final foot containing only one heavy syllable, which is preceded by a trochee, while penultimate stress has a different underlying foot structure, that is, a final trochee preceded by an unparsed syllable (Domahs, Klein, et al, 2013;Domahs et al, 2008;Janben & Domahs, 2008;Röttger et al, 2012). In consequence, APU versus F stress patterns are phonologically more similar than APU versus PU patterns and should thus be more difficult to keep distinct in a mental representation for participants who have acquired this aspect of German phonology.…”
Section: Discussionsupporting
confidence: 70%
“…In the word stress version of the PRA we used different types of stress patterns, which have been claimed to have different (antepenultimate vs. penultimate stress) or analogous (antepenultimate vs. final stress) phonological representations. Specifically, it has been argued that both antepenultimate and final stress patterns have the same underlying foot structure, that is, a final non-branching foot consisting of a heavy syllable which is preceded by a trochee, while the penultimate stress pattern has a different underlying foot structure, that is, a final trochee preceded by a unparsed syllable (Domahs, Klein, et al, 2013;Domahs, Wiese, Bornkessel-Schlesewsky, & Schlesewsky, 2008;Janben & Domahs, 2008;Röttger, Domahs, Grande, & Domahs, 2012). In consequence, it may be more difficult to keep distinct phonological representations of antepenultimate versus final stress compared to representations of penultimate versus antepenultimate or final stress.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Although in general the target non-words lead to different specific stress assignment preferences depending on their syllable structure (e.g., words with V.VC.V structure are preferably stressed on PU syllable), there is always a large degree of interindividual variance – which so far is left unexplained – such that in no condition non-words are exclusively stressed on one syllable (Janssen, 2003b; Tappeiner et al, 2007; Röttger et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Féry (1998) found that 73% of German bisyllabic words are stressed on the penult. In this light, it has been debated whether in German the penultimate stress pattern can be regarded as the default (e.g., Eisenberg, 1991; Kaltenbacher, 1994; Wiese, 1996; Levelt et al, 1999) or not (Giegerich, 1985; Vennemann, 1991; Féry, 1998; Domahs et al, 2008; Janssen and Domahs, 2008; Roettger et al, 2012). …”
Section: Introductionmentioning
confidence: 99%